2015
DOI: 10.1038/srep13811
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of digital PCR platforms and semi-nested qPCR as a tool to determine the size of the HIV reservoir

Abstract: HIV persists in latently infected cells of patients on antiretroviral therapy (ART). This persistent proviral DNA reservoir is an important predictor of viral rebound upon therapy failure or interruption and forms a major obstacle towards cure. Accurate quantification of the low levels of persisting HIV DNA may aid patient monitoring and cure research. Digital PCR is a promising tool that enables direct absolute quantification with high sensitivity. With recent technological advances, several platforms are ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 47 publications
5
61
1
Order By: Relevance
“…If reaction volumes for qPCR and dPCR are equal, sensitivity of both platforms have been shown to be comparable [47]. Notably, false-positive partitions have been encountered on several dPCR platforms and can cause a decrease in sensitivity [15,16,45,46]. These false positives seem assaydependent and may also differ between the dPCR platform used [15,46].…”
Section: Analytical Sensitivitymentioning
confidence: 92%
See 3 more Smart Citations
“…If reaction volumes for qPCR and dPCR are equal, sensitivity of both platforms have been shown to be comparable [47]. Notably, false-positive partitions have been encountered on several dPCR platforms and can cause a decrease in sensitivity [15,16,45,46]. These false positives seem assaydependent and may also differ between the dPCR platform used [15,46].…”
Section: Analytical Sensitivitymentioning
confidence: 92%
“…For HIV, Strain et al [16] showed a 4-to 20-fold decrease in coefficient of variation (CV) for HIV pol and 2-LTR quantification. When ddPCR was compared with a seminested qPCR for HIV quantification, ddPCR was more precise for measuring HIV DNA [46], but showed an equal precision for the quantification of HIV RNA forms [15]. For CMV, Hayden et al [12] and Sedlak et al [47] found a higher precision at high CMV concentrations, although equal precision was found for lower levels of CMV.…”
Section: Increased Precisionmentioning
confidence: 94%
See 2 more Smart Citations
“…More recently, an assay that dispenses with the extraction step has been proposed (70). Recent technical progress has permitted the development of HIV DNA quantification by digital droplet PCR (ddPCR), which does not require an external quantification standard (71)(72)(73)(74)(75)(76)(77). However, some false-positive signals have been observed with ddPCR, which can be a problem when this method is used for diagnosis (76).…”
Section: Dna Load In Resting Cd4mentioning
confidence: 99%